2021
DOI: 10.1016/j.ajem.2021.01.065
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 lockdown on infectious diseases epidemiology: The experience of a tertiary Italian Pediatric Emergency Department

Abstract: The aim of this study was to describe the rate and types of community-acquired respiratory infections observed in a pediatric ED during the SARS-CoV-2 related lockdown in Italy and to compare data with the same period of previous year. Methods: A retrospective analysis of medical charts of patients arrived at the ED of Gaslini Children's Hospital from 10th March 2020 to 30th April 2019 and the same frame of 2020 were performed. We compared two groups by demographics, duration of fever before ED admission, tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 14 publications
5
36
0
1
Order By: Relevance
“…The observed reduction probably reflects the real incidence of this infection because the few cases of these complications (PM and CSEI) were seen during the harder days of the lockdown (March and April). Other authors have demonstrated a similar trend in child infections at the emergency department [ 24 ].…”
Section: Discussionsupporting
confidence: 57%
“…The observed reduction probably reflects the real incidence of this infection because the few cases of these complications (PM and CSEI) were seen during the harder days of the lockdown (March and April). Other authors have demonstrated a similar trend in child infections at the emergency department [ 24 ].…”
Section: Discussionsupporting
confidence: 57%
“…Outside the U.S., studies conducted during the first months during lockdown involving pediatric emergency departments in France, Italy, and New Zealand showed significant reductions in emergency visits of children with respiratory disease in a wide age range (28). A reduction in AOM episodes during lockdown was reported from the U.S., Italy, and France from general pediatric (26,29) and emergency room settings (28,30,31). A high rate of improvement in children with chronic otitis media with effusion (OME) was also reported during lockdown (29,32).…”
Section: Discussionmentioning
confidence: 99%
“…The number of EV-positive samples associated with HFMD/exanthema received in the lab increased over the years of the study period, until March 2020 where they dropped sharply due to the COVID-19 pandemic, as has occurred with other transmissible diseases [ 38 ]. The explanation could be in increased circulation of CVA6 with a more visible clinic manifestations and also greater interest of clinicians in EV surveillance, as has occurred in other European countries in recent years [ 22 , 36 ].…”
Section: Discussionmentioning
confidence: 99%